Kardiochirurgia Dorosłych Surgical treatment of thoraco-abdominal aneurysms. Early experience - Krasoń, Marcin; Zanetti, Pietro Paolo; Okita, Yutaka; Przybylski, Roman; Pacholewicz, Jerzy; Nadziakiewicz, Paweł; Głowacki, Jan; Knapik, Piotr; Zembala, Marian (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2007)
Background: Surgical treatment of thoraco-abdominal aneurysms is still a difficult issue bringing a high risk of serious complications. Aim: The aim of the study was to analyze retrospectively methods of surgical treatment and their results in a group of 5 patients treated in our centre. Material and methods: Five patients (1 woman and 4 men) with diagnosis of enlargement of thoraco-abdominal aorta were treated surgically with two techniques of extracorporeal circulation (total cardiopulmonary bypass – 2 patients, and partial left heart bypass with biopump – 3 patients) Mean age in the group was 43 ± 11 years (range 28-57). Aetiologies of the aneurysms were as follows: Marfan syndrome (1); Marfan syndrome and chronic aortic dissection (1); chronic aortic dissection (1), degenerative aneurysm (2). Results: All patients in the group survived the procedure. There was no paraplegia observed. One patient presented transient renal failure, and two patients due to lymphorhea presented prolonged wound healing. Mean hospital stay in the analyzed group was 32.6 ± 28.1 days. Conclusions: The outcome of the first attempts at surgical treatment of extensive thoracoabdominal aneurysms is satisfactory; nevertheless, there is a risk of numerous potential complications and high treatment costs.